ASSESSMENT OF SATISFACTION LEVELS OF ADMITTED PATIENTS IN A TERTIARY CARE PRIVATE HOSPITAL OF LAHORE - Muhammad Luqman Farrukh Nagi (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: This study was done to assess the opinion of patients regarding the services of a tertiary care hospital in Lahore. DESIGN: Cross-sectional study. METHODS: It was conducted on a convenient sample of 200 available patients admitted in Shalamar Hospital, Lahore during the months of July to August 2016. A modiﬁed, pretested, structured Picker Patient Experience (15) questionnaire was used. Informed consent was obtained from the participants. Conﬁdentiality and anonymity of the participants was preserved. Data entry was done on SPSS version 23 for Microsoft Windows. RESULTS: The department of interview of all participants was; general outdoors 39.5% (n=79), private outdoors 13.5% (n=27), accident and emergency 41% (n=82) and private rooms 6 % (n=12). Among all, 23% (n=46) were uneducated, 22% (n=44) or attained education till primary school, 34% (n=68) were matriculated and 21% (n=42) were educated till bachelors and above. A signiﬁcant (p =0.003) association between cleanliness of hospital toilets and bathrooms and overall experience of a patient in hospital setting exists. Only 7% (n=14) of the surveyed patients were not satisﬁed with respect and dignity towards them. A good 56.5% (n= 113) were satisﬁed with their experience at the hospital, whereas another 39.5% (n=79) rated the services of the hospital as good. Only 4% (n=8) of the admitted patients were not satisﬁed with the hospital services. CONCLUSION: The overall experience of the patients in terms of physical comfort, timeliness, respect, dignity, assistance and responsiveness towards patients visiting this setting was satisfying. Periodic patient satisfaction survey should be institutionalized for further research.